Pengaruh Model Problem Basic Learning Dengan Teknik Mind Mapping Terhadap Kemampuan Berpikir Kritis dan Pengetahuan Metakogitif Siswa Sekolah Menengah Pertama - Chintani Sihombing; Deswidya S Hutauruk; Salim Efendi (Jurnal Pendidikan Biologi, 2018)
The research was conducted aimed at knowing the effect of the Problem Based Learning model with Mind Mapping techniques influencing critical thinking skills and metacognitive knowledge of junior high school students. The sample of this study was class IX in SMP Negeri 1 Ronggur Nihuta which was taken by random sampling with the number of students 62. The instrument of this research was a test. This research method is descriptive and data analysis techniques using the t test with a significance level α = 0.05. The results showed that the influence of the Problem Based Learning model with Mind Mapping techniques had an effect on students' critical thinking skills (tcount 90.66> t table 2.039); (2) There is the influence of the Problem Based Learning model with the Mind Mapping technique affecting the metacognitive knowledge of students (t count 40.68> t table 2.039). The results of this study imply that the level of critical thinking skills, metacognitive knowledge has an important role in improving the learning outcomes of junior high school students.